Thinking outside the box – a vision of ambient learning displays. (15th February 2012) - Börner, Dirk; Kalz, Marco; Specht, Marcus
With a focus on the situated support of informal and non-formal learning scenarios in ubiquitous learning environments, the presented paper outlines the authors' vision of ambient learning displays – enabling learners to view, access, and interact with contextualised digital content presented in an ambient way. The vision is based on a detailed exploration of the characteristics of ubiquitous learning and a deduction of informational, interactional, and instructional aspects to focus on. Towards the vision essential research questions and objectives as well as a conceptual framework that acquires, channels, and delivers the information framed in the learning process are presented. To deliver scientific insights into the authentic learning support in informal and non-formal learning situations and to provide suggestions for the future design of ambient systems for learning the paper concludes with a research agenda proposing a research project including a discussion of related issues and challenges.